2021
DOI: 10.1590/1678-4324-2021200319
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Alkaline Pectinase Productive Bacillus tropicus from Fruit and Vegetable Waste Dump Soil

Abstract: Alkaline pectinase is the utmost significant industrial enzyme of the bioscouring process. By considering bio scouring of cotton, 30 microbial isolates from fruit and vegetable waste rich dump soil of Solang Valley and Vasishta (Manali, Himachal Pradesh, India) were isolated and screened for the alkaline pectinase production in the current research work. Only four isolates P3, P16, P21, and P27 were capable to produce extracellular alkaline pectinase at pH 9. Further by applying submerged fermentation, the alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In this study, enzyme production was observed at temperatures ranging from 30 to 60 • C with pectinase maximum production at 30 • C with the enzymatic activity of 8.56 UI (Figure 4C). The findings correspond with those by Tepe and Dursun [87], which showed the ideal temperature for pectinase production by Bacillus pumilus at 30 • C; Ibrahim et al [88] and Thakur et al [89] also recorded similar findings for Aspergillus niger HFD5A-1 and for Bacillus tropicus at 37 • C, respectively.…”
Section: Effect Of Temperaturesupporting
confidence: 89%
“…In this study, enzyme production was observed at temperatures ranging from 30 to 60 • C with pectinase maximum production at 30 • C with the enzymatic activity of 8.56 UI (Figure 4C). The findings correspond with those by Tepe and Dursun [87], which showed the ideal temperature for pectinase production by Bacillus pumilus at 30 • C; Ibrahim et al [88] and Thakur et al [89] also recorded similar findings for Aspergillus niger HFD5A-1 and for Bacillus tropicus at 37 • C, respectively.…”
Section: Effect Of Temperaturesupporting
confidence: 89%
“…B. tropicus JMT retains several anthrax-like virulence genes and displays different characteristics, such as B. cereus G9241 and B. cereus 03BB87, not the non-pathogenic B. tropicus strain [ 39 , 40 , 41 ]. In previous studies, these atypical B. cereus strains have been widely accepted to overcome host immunity and cause severe symptoms, even death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the biochemical characterization of the studied pectinase also showed high performance under alkaline, thermophilic, and halophilic conditions. There are several reports on alkaline and thermostable pectinase enzymes from various geographic locations and sources, particularly from agro- and industrial-wastes ( Khatri et al, 2015 ; Oumer and Abate, 2017 ; Yu et al, 2017 ; Thakur et al, 2021 ). Regarding soda lakes, only two occurrences of pectin breakdown have thus far been described, both of which describe unique species of the phylum Bacteroidota belonging to the genera Alkaliflexus and Natronoflexus ( Sorokin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%